PENINGKATAN KEMAMPUAN SISWA KELAS IX.1 MENULIS BAHASA INGGRIS NARRATIVE TEXT DENGAN MEDIA GAMBAR SERI SMPN 1 GUNUNG TOAR KECAMATAN GUNUNG TOAR - Yusni Yusni (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2018)
The reseach is a classrom action reseach by using the media image series in improving the ability of writingnarrative text grade student IX.1 SMPN 1 Gunung Toar sub- districs Gunung Toar with the student amount 20persons. The reseach result from teacher activity the data obtained in cycle I the first meeting amounted to58,3% and the second meeting of 70,8%. The data of the cycle II on the activity of the teacher meeting the first at75% and second meeting amounted to 83,3%. The activities of students in cycle I of meeting I obtained by 58%and meeting 2 for 66,7%, while in the cycle II meeting I by 75% and meeting 2 of 83%. The ability to writenarrative text in reseach will be described using the averages class that starts on the initial data of 65,4increased in cycle I by 75 and an cycle II of 90 the avrage class. Therefore the use of media images series canimprove the ability of writing narrative text.